KNEE TUBERCULOSIS UNDER ANTITUBERCULOUS CHEMOTHERAPY; A CASE REPORT - Duygu Geler,; Nurben Süldür,; Şebnem Ataman,; Mesut Birol Atay,; Şebnem K. Ayva, (Archives of Rheumatology, 2004)
Tuberculosis of the knee is the third common site of skeletal tuberculosis after the spine and the hip. In this case, a patient, who was previously operated due to Mall de Pott, has developed tuberculous arthritis in her right knee under antituberculous chemotherapy. In such cases a drug resistance should not be forgetten and in differential diagnosis, tuberculosis should not be underestimated.